HUBUNGAN TINGKAT PENGETAHUAN PASIEN TENTANG PENYAKIT HERNIA DENGAN KEJADIAN HERNIA DI POLI BEDAH RSUD WONOSARI - I Dewa Gede Kariasa; Anida Anida; Suswatiningsih Suswatiningsih (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2018)
Background: There has been hernia occurrence on November 15 th, 2016 in RSUD Wonosari.  The number of Hernia inguinalis patients from January until October 2016 was 145 people. This  ﬁgure consisted of  143 (98.60) male patients and 2 (1.30%) female patients. Objective: The study aimed at identifying the Relationship between the Patients’ Knowledge Level Regarding Hernia and the Hernia Occurrence in the Surgery Polyclinic of RSUD Wonosari. Method: The study was an analytic descriptive research by cross-sectional approach. For the sampling technique, the researchers selected the quota sampling technique. The population in this study was 300 people, while the sample that had been selected for this study was 75 respondents. The data were gathered through questionnaire distribution. The researchers also performed bivariate analysis by means of Chi Square test. Results: The results of this study showed that 24.00% of the respondents had good knowledge level regarding hernia, 32.00% of the respondents had moderate knowledge level regarding hernia, and 44.00% of the respondents had poor knowledge regarding hernia. The number of hernia patients from March 6 th March 25 th, 2016, was 9 people. From the results of signiﬁ cance test, the researchers found the sig. value = 0.001.Conclusion: There has been signiﬁ cant relationship between the knowledge level regarding hernia and the hernia occurrence in the Surgery Polyclinic of RSUD Wonosari.